(untitled) (Perner’s Contacts, 2018)
Transport as a modern and dynamic segment is constantly developing rapidly. It reflects the demands of faster, more efficient and safer transport, on the other hand it brings with it the risk of emergency events with negative consequences for the life, health of the population and the environment. The assessment of the consequences of mobile accident hazards has been solved in the European Union marginally. The issue of assessing and evaluating mobile sources of risk is not regulated by law and therefore there is insufficient pressure to manage and reduce risks. The aim of the present contribution is to point out that the transport of dangerous substances, in terms of the nature of transported material, presents a special hazard in the event of an emergency, especially for humans. Leaked toxic or flammable substances may endanger the life and health of many people. The contribution of this article is also a practical example detailed assessment of risks related to the transport of hazardous substances by road.